PENGARUH DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR BADAN URUSAN LOGISTIK KABUPATEN SIDENRENG RAPPANG - Andi Firdayana Pacoweri; Gazali Amin; Auliyah Nurwafiyyah (Universitas Ichsan Sidenreng Rappang, 2026)
Work discipline is one of the important factors affecting employee performance within an organization, particularly in government institutions. The problem addressed in this study is the suboptimal employee performance, which is presumed to be influenced by the level of employees’ work discipline. This study aims to analyze the effect of work discipline on employee performance at the Regional Office of the Logistics Affairs Agency (BULOG) of Sidenreng Rappang Regency. This study employed a quantitative research method with a survey approach. Data were collected through the distribution of questionnaires to respondents and were analyzed using statistical analysis techniques. The results indicate that work discipline has a positive and significant effect on employee performance. This is evidenced by the t-test result, where the calculated t-value of 4.554 is higher than the t-table value of 2.034, with a significance value of 0.000, which is lower than 0.05. Furthermore, the coefficient of determination (R²) result shows a value of 0.357, indicating that 35.7% of the variation in employee performance can be explained by work discipline, while the remaining 64.3% is influenced by other factors outside the scope of this study. Therefore, it can be concluded that improving work discipline plays an important role in enhancing employee performance at the Regional Office of the Logistics Affairs Agency (BULOG) of Sidenreng Rappang Regency.